Lula-Lá e o PT em Circulação nas Charges de Angeli, um Estudo em Análise Crítica do Discurso. - Batistel, Silmara Siqueira (2010)
The objective of this research is to develop an analysis of the of the galley of charges of political inclination of Angeli published in Folha de São Paulo, under the focus of Critical Discourse Analysis, postulated by Teun A. Dijk. It is discussed the representation and the materialization of the political discourse. The study of the political charges concerns to the dicotomy humor/politics that permeates the main supports of midia communication in the 21 century The charges of Angeli constitutes a representation of the politician s image and a breaking with the mental models and the ideological configuration of the discourse uttered by such representatives, because it establishes a compare among the imagetic discourse that refracts the politician s illustration, specifically, president Lula, and the sociopolitical and economic context that goes up to the period of the PT government . Therefore, it is pertinent to understand the context in that charges were produced, seeking to analise the values that characterize it and the polyphonic speech and intertextual that composes the style of the gender, as well as of the author, the discourse concepts based in the theoretical meaning of ACD will discuss, in fact, in the studies Van Dijk and ists considerations concerning the categories Access, Ideology, Power and Mental Models that permeate the discourses.